2007
DOI: 10.1007/s12038-007-0030-3
|View full text |Cite
|
Sign up to set email alerts
|

Chondroprotective potential of root extracts of Withania somnifera in osteoarthritis

Abstract: This is the first report describing two novel chondroprotective activities of aqueous extracts of Withania somnifera root powder.First,these extracts had a statistically significant,short-term chondroprotective effect on damaged human osteoarthritic cartilage matrix in 50% of the patients tested. Second,these extracts caused a significant and reproducible inhibition of the gelatinase activity of collagenase type 2 enzyme in vitro.

Help me understand this report

Search citation statements

Order By: Relevance

Paper Sections

Select...
3
1
1

Citation Types

0
26
0

Year Published

2008
2008
2020
2020

Publication Types

Select...
5
3
1

Relationship

1
8

Authors

Journals

citations
Cited by 50 publications
(26 citation statements)
references
References 10 publications
0
26
0
Order By: Relevance
“…MMP-1, -3, -9 and -13, and ADAMTS-5 were down regulated when compared with untreated arthritic or AEC-CP-NC-treated mice, indicating that the observed reduction is due to the efficacy of the nanoformulated LG. Studies on the chondroprotective effects of W. somnifera, a key ingredient of LG, have shown similar results in which treatment on cartilage explants from OA patients not only increased the release of proteoglycans, but had a direct dosedependent inhibitory effect on the gelatinase activity of collagenase type II [43]. Another similar study looked at the protective effect of W. somnifera against the degradation of collagen by collagenases, and demonstrated that the herbal induced a 71% inhibition of degradation of the extracellular matrix components in bovine tissue.…”
Section: Discussionmentioning
confidence: 77%
“…MMP-1, -3, -9 and -13, and ADAMTS-5 were down regulated when compared with untreated arthritic or AEC-CP-NC-treated mice, indicating that the observed reduction is due to the efficacy of the nanoformulated LG. Studies on the chondroprotective effects of W. somnifera, a key ingredient of LG, have shown similar results in which treatment on cartilage explants from OA patients not only increased the release of proteoglycans, but had a direct dosedependent inhibitory effect on the gelatinase activity of collagenase type II [43]. Another similar study looked at the protective effect of W. somnifera against the degradation of collagen by collagenases, and demonstrated that the herbal induced a 71% inhibition of degradation of the extracellular matrix components in bovine tissue.…”
Section: Discussionmentioning
confidence: 77%
“…Aliquots 4,8,12,16,20, and 24 µL of working standards (50 µg mL −1 ) were applied to the HPTLC plates for preparing six-point calibration curves. The extracts were also subjected to HPTLC for separation and quantification of withanolides.…”
Section: Preparation Of Standard Solutionsmentioning
confidence: 99%
“…Pharmacological action also includes physiologic and metabolic restorations. Thus, it is effective in the treatment of arthritis, geriatric condition, behavioral, neurodegenerative disorders, and stress-related problems [16,17]. These medicinal values are mainly attributed to withanolides present in the roots of W. somnifera [18].…”
Section: Introductionmentioning
confidence: 99%
“…Further studies have revealed that, extract of the root powder of Ashwagandha (Withania somnifera) has been found to have chondro-protective effect on the damaged human osteoarthritic cartilage matrix in 50% of the patients and hence prevent further degeneration of bones and is also found to be beneficial in Osteoarthritis (Sumantran, 2007;Bhatt, 2007). Panchtikta guggulu Ghrita, Mahanarayana Taila and Janu vasti are mentioned for the management of Sandhigata vata in Ayurvedic texts and have also been proved efficacious in several studies (Kumar, 2017).…”
Section: Discussionmentioning
confidence: 99%